2009
DOI: 10.1007/s11671-009-9251-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monodisperse Nanocrystals via Microreaction: Open-to-Air Synthesis with Oleylamine as a Coligand

Abstract: Microreaction provides a controllable tool to synthesize CdSe nanocrystals (NCs) in an accelerated fashion. However, the surface traps created during the fast growth usually result in low photoluminescence (PL) efficiency for the formed products. Herein, the reproducible synthesis of highly luminescent CdSe NCs directly in open air was reported, with a microreactor as the controllable reaction tool. Spectra investigation elucidated that applying OLA both in Se and Cd stock solutions could advantageously promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
1
21
1
2
Order By: Relevance
“…Mejia‐Ariza and Huskens used a multi‐inlet vortex mixer (MIVM) to form supramolecular gold aggregates, which demonstrated a robust and scalable process with high loading capacity relative to laminar flow MDs (Figure c). Other type of micromixers reported in tubular microreactors include convective mixer (Figure e), slit interdigital micromixer, central‐collision‐type micromixer, or K–M mixer (Figure f) . All these micromixers share a similar ultimate goal of breaking the fluid flow, shortening the diffusion distance, and therefore achieving a better micromixing performance.…”
Section: Classification Of Microfluidic Synthesis Systemsmentioning
confidence: 99%
“…Mejia‐Ariza and Huskens used a multi‐inlet vortex mixer (MIVM) to form supramolecular gold aggregates, which demonstrated a robust and scalable process with high loading capacity relative to laminar flow MDs (Figure c). Other type of micromixers reported in tubular microreactors include convective mixer (Figure e), slit interdigital micromixer, central‐collision‐type micromixer, or K–M mixer (Figure f) . All these micromixers share a similar ultimate goal of breaking the fluid flow, shortening the diffusion distance, and therefore achieving a better micromixing performance.…”
Section: Classification Of Microfluidic Synthesis Systemsmentioning
confidence: 99%
“…They demonstrated that the formation and tuning of droplets within the microreactor can help to fine-tune the size and shape of nanoparticles. Recently, microreactors have been used to synthesize, mostly, semiconducting nanomaterials such as CdSe and TiO 2 [22]. However, few reports show that in continuous flow microreactor, for a multi-reactant system, mixing largely occurs by molecular diffusion and micromixers may be needed [17,22,23].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Recently, microreactors have been used to synthesize, mostly, semiconducting nanomaterials such as CdSe and TiO 2 [22]. However, few reports show that in continuous flow microreactor, for a multi-reactant system, mixing largely occurs by molecular diffusion and micromixers may be needed [17,22,23]. Nevertheless, these studies reveal the potential of continuous flow microreactors for scalable synthesis of nanoparticles.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Para tal, a reação deve ser controlada para assegurar que a nucleação tenha um período tão curto quanto possível e não mais ocorra agregação e coagulação de partículas individuais durante o crescimento. (NAKAMURA et al, 2004;YANG et al, 2009;MARRE e JENSEN, 2010;LIU et al, 2014;LIN et al, 2015;WATT et al, 2015;MA et al, 2017;SWAIN et al, 2017) A microfluídica é utilizada para obter nanopartículas com maior monodispersão em comparação a métodos tradicionais, que requerem etapas posteriores de purificação para este fim. (SONG et al, 2008;HARTMAN e JENSEN, 2009;YANG et al, 2009)(DITTRICH, 2005MA et al, 2017 segundos, produzindo alta eficiência quântica (35-55%) e mantendo uma faixa de FWHM estreita (26 -31 nm), importante para uma distribuição monodispersa.…”
Section: Síntese De Quantum Dots Em Fluxounclassified
“…Devido à sua capacidade de separar os estádios de nucleação e crescimento na formação de nanopartículas de modo controlado. Nanopartículas com maior uniformidade e menor índice de polidispersividade podem ser preparadas dentro de plataformas microfluídicas com desempenho melhorado, como mencionamos anteriormente (HARTMAN e JENSEN, 2009;YANG et al, 2009;WATT et al, 2015;MA et al, 2017). Na Tabela 1 pode-se observar a variedade de formas e métodos para síntese de nanopartículas metálicas em plataformas microfluídicas para facilitar a comparação entre os seus tipos, tamanho, forma e o substrato da plataforma microfluídica.…”
Section: Síntese De Nanopartículas Metálicas Em Fluxounclassified